Current clinical translation of microbiome medicines. (April 2022) - McCoubrey, Laura E.; Elbadawi, Moe; Basit, Abdul W.
Abstract : The microbiome is experiencing increasing scrutiny for its role in disease, and the number of new research reports describing microbiome–disease relationships is growing exponentially. Researchers are increasingly working to translate the emerging fundamental science into microbiome medicines that will address important unmet needs in the clinic. We summarise the types of microbiome medicines that have the most translational potential, and provide a detailed analysis of the current global microbiome medicines pipeline and the challenges facing clinical translation. The regulatory pipeline is currently dominated by probiotics intended for oral delivery to the gastrointestinal (GI) tract; however, several non-living biologics and small molecules provide notable exceptions. With the first microbiome medicine set to begin the regulatory submission process in 2022, it is an exciting time for the field. Highlights: As the mechanisms underpinning disease–microbiome associations are elucidated, many opportunities for the design and development of novel microbiome therapeutics are emerging. Microbiome medicines can be broadly grouped into two categories: living microorganisms (e.g., probiotics) and non-living therapeutics (e.g., postbiotics, prebiotics, and peptides). At present the global microbiome medicines pipeline demonstrates a key focus on oral formulations incorporating probiotics for the treatment of gastrointestinal disease. One such therapy, developed by Seres Therapeutics for recurrent Clostridioides difficile infection, is set to begin the regulatory submission process in early 2022. Notable non-living therapeutics undergoing the regulatory approval process include the small molecule sibofimloc indicated for Crohn's disease, a multi-peptide vaccine for glioblastoma/adrenal cancer, and an inactivated bacterium for dermatological disease. To increase successful translation of microbiome medicines, several challenges may be faced, such as overcoming interindividual variation in microbiome composition and confounding variables in clinical trials.